PENGARUH DPK, PEMBIAYAAN MUDHARABAH, NPF TERHADAP ROA BANK UMUM SYARIAH DI INDONESIA - Hodi, Hodi; Wardana, Guntur Kusuma (I-Economics, 2023)
In Islamic banks, one of the indicators commonly used to assess the bank's health is its own financial report. Information obtained from financial reports can be used to calculate various financial ratios, often serving as the basis for evaluating a bank's health. Several factors affect profitability in Islamic banks, sourced from the different profitability indicators generated by various performance metrics. This is because third-party funds (DPK) and Mudharabah financing, when increasing, contribute to the increase in the Return on Assets (ROA). This is due to the fact that an increase in customer deposits gathered by Islamic banks will enhance the efforts of the Islamic bank in generating profitability. On the other hand, if non-performing financing (NPF) increases, the ROA will decrease. This is because the non-acceptance of disbursed funds contributes to the decline in ROA. The research aims to investigate the partial and simultaneous effects of DPK, Mudharabah financing, and NPF on ROA. The research methodology employed is quantitative with a causal approach. Using purposive sampling technique, five Islamic commercial banks were selected as the research sample for the period 2017 to 2022. The analysis utilized panel data regression analysis through Eviews12. The results indicate that DPK and Mudharabah financing, individually, do not have a significant partial impact on the ROA of Islamic commercial banks. However, NPF has a significant partial effect on the ROA of Islamic commercial banks. Furthermore, when considered collectively, DPK, Mudharabah financing, and NPF have a significant simultaneous impact on the ROA of Islamic commercial banks.